Transformasi Sampah Menjadi Sumber Daya: " Dalam Penyuluhan Pengelolaan kompos di Komunitas Parisada Hindu Dharma Semarang Selatan - Ni Komang Ayu Artiningsih, Ayu; Nurtekto (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
This outreach examines efforts to transform waste into resources through education on compost management in the South Semarang Hindu Parisada Dharma Community. The education aims to raise awareness among the public about the importance of managing organic waste by composting as a strategy to support environmental sustainability. Suitable compost management methods tailored to community needs are selected and promoted, involving community leaders and local groups to ensure active participation and deep understanding of the waste recycling process. The outcomes of this outreach are expected to make a positive contribution by reducing the volume of organic waste going to landfills and enhancing the utilization of local potential to support overall environmental sustainability. Transforming organic waste into compost not only mitigates negative environmental impacts but also makes the community engagement initiative focused on compost management in the South Semarang Hindu Parisada Dharma Community relevant and strategic. This program is anticipated to empower the community to manage organic waste as a resource with economic and ecological value. By leveraging local potential and community wisdom, this effort can serve as an inspiring example for other communities in promoting environmental sustainability and reducing the negative impacts of waste management in general.